Bead-Based Hydrodynamic Simulations of Rigid Magnetic Micropropellers - Codutti, Agnese; Bachmann, Felix; Faivre, Damien; Klumpp, Stefan (Frontiers in Robotics and AI, 2018)
The field of synthetic microswimmers, micro-robots moving in aqueous environments, has evolved significantly in the last years. Micro-robots actuated and steered by external magnetic fields are of particular interest because of the biocompatibility of this energy source and the possibility of remote control, features suited for biomedical applications. While initial work has mostly focused on helical shapes, the design space under consideration has widened considerably with recent works, opening up new possibilities for optimization of propellers to meet specific requirements. Understanding the relation between shape on the one hand and targeted actuation and steerability on the other hand requires an understanding of their propulsion behavior. Here we propose hydrodynamic simulations for the characterization of rigid micropropellers of any shape, actuated by rotating external magnetic fields. We approximate the shape of micropropellers by an ensemble of rigidly connected spheres, for which the mobility matrices can be calculated via the method of reflections. We characterize the influence of model parameters such as bead size, distance between beads and magnetic properties on the swimming behavior of helical propellers to identify optimal simulation parameters. We then apply the simulation to randomly shaped propeller, specifically to a recently characterized propeller shape and study their frequency- dependent swimming behaviors. The simulations show that the orientation of the magnetic moment with respect to the propeller’s internal coordinate system has a strong impact on the propulsion behavior and has to be known with a precision of ≤ 5 ◦ to predict the propeller’s velocity-frequency curve. This result emphasizes the importance of the magnetic properties of the micropropellers for the design of desired functionalities for potential biomedical applications, and in particular the importance of their orientation within the propeller’s structure.